Resetting in Citrus Groves - Mongi Zekri (EDIS)
To maintain the overall productivity of a citrus grove, dead or declining trees should be promptly removed and replaced with young, healthy trees, a practice known as resetting. Resetting presents many challenges for growers because young trees require more attention and care than more established trees. This 4-page fact sheet discusses effective resetting methods and maintenance for citrus. Written by Zekri Mongi, and published by the UF Department of Horticultural Sciences, August 2015.